Optimasi Jaringan Pipa Sumur ESP Pada Manifold A dan Manifold Satelite untuk Meningkatkan Laju Aliran Minyak dan Analisis Perubahan Tekanan di Lapangan J - Eriska Eklezia Dwi Saputri; Hadziqul Abror; Pedraza, Putri Rizkika Ramadhanti; Ayuningtyas, Rivanya (Journal of Sustainable Energy Development, 2024)
The wells in Field J, using Electrical Submersible Pumps (ESP), have replaced their natural flow operations. To optimize this ESP well and pipeline network, the research focuses on adjusting the ESP pump frequency within the Pipesim simulator, increasing it to enhance oil flow rates. This study employs a quantitative approach, where field data is analyzed and input into a simulation model that replicates real-world conditions. The analysis encompasses changes in flow rates and pressures, comparing the base case to post-optimization simulations. The results indicate a substantial increase in the initial oil flow rate from 578 STB to 720 STB/d, with an increase of 142 STB/d, when the pump frequency is raised to 60 Hz. This frequency adjustment significantly boosts pump discharge pressure, providing the added energy needed to transport fluid to the surface. Keyword: esp; pipeline network; production optimization; production simulation